EPC in the Nordic countries : EPC Nordic - Lindseth, Liv Randi (TemaNord ;, 2015)
Present market status; Comparison and recommendations; Abbreviations; 1. Introduction; 1.1 Methodology; 1.2 What is Energy Performance Contracting; 1.3 Structure; 2. Denmark; 2.1 The EPC market in Denmark; 2.1.1 Short history; 2.1.2 Number of projects; 2.1.3 The EPC Providers; 2.1.4 The EPC Clients; 2.1.5 The EPC Facilitators; 2.1.6 Summary; 2.2 National characteristics; 2.2.1 The national EPC model; 2.2.2 Legal and financial support schemes; 2.2.3 A typical EPC project; sector, size, savings; 2.2.4 The most recent projects; 2.2.5 Upcoming official Danish Standard for EPC